Student 5.0: immersive learning in next-gen Automation of Manufacturing Systems courses for the Industry 5.0 era - Ramírez-Cedillo, Erick; Armendáriz-Rodríguez, Maximiliano; García-Ávila, Josué; Quintero-Sánchez, Diego; Ortiz-Espinoza, Alexandro Antonio; Vargas-Martínez, Adriana (Frontiers in Education, 2025)
This manuscript introduces an educational approach by integrating Industry 4.0 and 5.0 technologies within a Smart Factory learning environment at Tecnologico de Monterrey (Tec) and through international collaboration with the Massachusetts Institute of Technology (MIT). It addresses the challenge of adapting engineering education to the demands of smart manufacturing, highlighting the importance of hands-on experience with cyberphysical systems, Additive Manufacturing (AM), Supervisory Control and Data Acquisition (SCADA) integration, and robotics. By integrating the curriculum with Sustainable Development Goals (SDGs), the initiative aims to train engineers capable of contributing to sustainable industrial practices and innovation. The Automation of Manufacturing Systems course provides immersive learning through direct engagement with advanced technologies and methodologies. Students develop technical skills in collaborative robots (cobots), human-machine interfaces (HMI), computer vision and Programmable Logic Controller (PLC) programming. This also develops methodological skills in analytical thinking problem-solving and other competences. The curricula further enhanced social and personal competencies, preparing students to lead in a technologically advanced and sustainable industrial environment. With the emergence of Industry 5.0, which emphasizes sustainability and worker wellbeing, this educational model integrates social behavior science with digital technologies in a student-centered approach. The presented case study highlights the effectiveness of redesigning the course to include immersive learning experiences focused on Industry 4.0 and 5.0 skills. A student survey conducted at the end of the course validated these findings, revealing high satisfaction levels (9.65/10) associated with developing new skills, exploring new concepts, generating new ideas, and promoting innovative thinking. Both the students and the teaching team offered recommendations to further scale and improve the course.